Incidence and Risk Factors of Cranial Nerve Palsy in Patients with Tuberculous Meningitis: A Retrospective Evaluation - Wen A; Cao WF; Liu SM; Zhou YL; Xiang ZB; Hu F; Wu LF; Cai W; Leng EL (Infection and Drug Resistance, 2023)
An Wen,1,2 Wen-Feng Cao,1,2 Shi-Min Liu,1,2 Yong-Liang Zhou,1,2 Zheng-Bing Xiang,1,2 Fan Hu,1,2 Ling-Feng Wu,1,2 Wen Cai,1,2 Er-Ling Leng3 1Department of Neurology, Jiangxi Provincial People’s Hospital (The First Affiliated Hospital of Nanchang Medical College), Nanchang, People’s Republic of China; 2Institution of Neurology, Jiangxi Provincial People’s Hospital (The First Affiliated Hospital of Nanchang Medical College), Nanchang, People’s Republic of China; 3Department of Pediatrics, Jiangxi Provincial People’s Hospital (The First Affiliated Hospital of Nanchang Medical College), Nanchang, People’s Republic of ChinaCorrespondence: Er-Ling Leng, Department of Pediatrics, Jiangxi Provincial People’s Hospital (The First Affiliated Hospital of Nanchang Medical College), No.92 Aiguo Road, Nanchang, 330006, People’s Republic of China, Tel +86791-8772-1401, Email wenan666@sina.comObjective: Tuberculous meningitis (TBM) is a common form of central nervous system (CNS) tuberculosis (TB). Cranial nerve palsy is a serious complication of TBM. Literature regarding this subject is still limited in China. This study evaluated the incidence of cranial nerve palsy in patients with TBM in South China, its association with the clinical forms of TB, and other patient characteristics.Methods: A retrospective chart review of patients with a diagnosis of TBM between January 2004 and December 2019 was conducted, and the demographic characteristics, clinical characteristics, and laboratory results of 114 patients were collected and followed up for 3 months. A multivariate logistic regression analysis model was used to explore the risk factors of cranial nerve palsy in patients with TBM.Results: A total of 114 patients were enrolled in this study. Cranial nerve palsy was observed in approximately 38 (33.3%) of TBM patients. Among them, 13 (28.3%) had optic nerve palsy, 24 (52.2%) had oculomotor nerve palsy, 5 (10.9%) had abducens nerve palsy, 2 (4.3%) had auditory nerve palsy, 1 (2.2%) had glossopharyngeal nerve palsy, and 1 (2.2%) had vagus nerve palsy. Using logistic regression analysis, focal neurological deficit, extracranial TB and cerebrospinal fluid (CSF) total white cell count (WCC) were shown to be risk factors for cranial nerve palsy.Conclusion: The prevalence rate of cranial nerve palsy was 33.3% in patients with TBM. Focal neurological deficits, extracranial TB and CSF total WCC are important predictors of cranial nerve palsy in patients with TBM.Keywords: tuberculous meningitis, tuberculosis, cranial nerve palsy, risk factors, prediction